Conductive and Porous Silicon Nanowire Anodes for Lithium Ion Batteries. Issue 7 (1st January 2017) - Hwang, Chihyun; Lee, Kangmin; Um, Han-Don; Lee, Yeongdae; Seo, Kwanyong; Song, Hyun-Kon
Abstract : Silicon nanowires (SiNWs) were prepared by chemically etching silicon wafers with silver nanoparticles. Their electrical conductivities and porosities were tuned by adjusting the doping concentration of silicon wafers from which the SiNWs were prepared. Porosity of the SiNWs were proportional to doping concentrations of the mother wafer because the dopant population provides nucleation sites for etching. The electrical conductivities of the doped SiNWs were 100 times higher than those of the intrinsic SiNW. However, there was no difference in the conductivity between two different doping level SiNWs ( Na = 2.7 × 10 15 and 5.7 × 10 19 ) due to the trade-off between porosity and the intrinsic conductivity of the solid backbone. The doping-dependent properties of SiNWs determined the capacity, stability and kinetics of the lithium alloying reaction of the SiNWs. The medium-level doping SiNWs, characterized by a mechanically obust porous structure, showed the most improved electrochemical performances in a full cell of a lithium manganese oxide || SiNW battery as a result of the balanced trade-off between coulombic efficiency and capacity retention.